DINAMIKA KOMUNIKASI INTERNAL DALAM AKTIVITAS YOGA MEMBENTUK PERILAKU SUSILA DI AMBARASHRAM, BANJAR NYUH KUNING, DESA MAS, KECAMATAN UBUD, KABUPATEN GIANYAR - G Juniartha, Made (WIDYA DUTA, 2012)
ABSTRACT Yoga teachings are universal. Yoga is a way to achieve harmony between the physical body, mind and soul or spirit as yoga movements can affect the physical and mental to be healthy, so that the soul is concentrated. In yoga activities, communication behavior to achieve the objectives expected by the yogic aspirant. When the communication occurred between the participants and the instructor or yoga teacher, there is a change in each participant. Changes are not only at physical level but also have a positive impact for the moral, mental and spiritual in the dynamics of the application or yoga practices that emphasize flexibility.The dynamics of internal communication in the activity of yoga can shape moral behavior of the participants in Ambarashram because of a verbal and nonverbal communication that lead to changes in both face to face communication, strengthen faith, increase self-introspection, and apply the teaching of tri kaya parisudha. By practicing yoga one can shape his or her moral behavior such as establishing calmness, speech control, and be kind to all creatures.The Dynamics of internal communication in yoga activities in Ambarashram shaped moral behaviors of its participants. It also provided a self-realization to the participants, for the purpose of yoga is to reach bliss by living harmoniously with other human being, human being and nature, and human being with God. Key words: dynamics, internal communication, yoga activities, moral behavior